2001
DOI: 10.1038/modpathol.3880278
|View full text |Cite
|
Sign up to set email alerts
|

Rosai-Dorfman Disease Isolated to the Central Nervous System: A Report of 11 Cases

Abstract: Sinus histocytosis with massive lymphadenopathy, also known as Rosai-Dorfman Disease (RDD), is an idiopathic histiocytic proliferation affecting lymph nodes. Although extranodal involvement has been reported in diverse sites, central nervous system (CNS) manifestation, particularly in the absence of nodal disease is uncommon. We report 11 cases of RDD primary to the CNS without evidence of other sites of involvement. The cases included 7 males and 4 females ranging in age from 22 to 63 years (mean: 41 y). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
162
0
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(176 citation statements)
references
References 34 publications
3
162
0
9
Order By: Relevance
“…Regions in the brain include dura, venous sinus, intraparenchymal, intraventricle area. 4 There were 36 cases reported RDD involving eyes were highly accompanied with nasal sinuses involvement. 2 The common ocular manifestations were soft tissue of the orbit and eyelids.…”
Section: Discussionmentioning
confidence: 99%
“…Regions in the brain include dura, venous sinus, intraparenchymal, intraventricle area. 4 There were 36 cases reported RDD involving eyes were highly accompanied with nasal sinuses involvement. 2 The common ocular manifestations were soft tissue of the orbit and eyelids.…”
Section: Discussionmentioning
confidence: 99%
“…Infection 5 has been suggested as an underlying cause, but a definitive agent has never been isolated.…”
Section: Aetiologymentioning
confidence: 99%
“…Molecular studies using polymorphic regions of the human and rogen receptor locus have demonstrated that RDD is a polyclonal disorder 5,8 .…”
Section: Aetiologymentioning
confidence: 99%
“…Occasional neutrophils and eosinophils may be seen and background fibrosis may be noted in extranodal disease. On immunohistochemical examination, histiocytes are immunoreactive for S-100 protein, HAM 56, α1 antitrypsin, α1 chymotrypsin, lysozyme, Mac 387 and Ki-1, but CD 1a and EMA are negative (2,10,16,20).…”
Section: Kutty Sa and Sreehari S: Rosai-dorfman Disease And Langerhanmentioning
confidence: 99%